2017
DOI: 10.2196/resprot.5744
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a Home Monitoring System for Heart Failure Patients: A Feasibility Study

Abstract: BackgroundImproving the management of patients with complex chronic disease is a substantial undertaking with the simultaneous goals of improving patient outcomes and controlling costs. Reducing avoidable hospitalization for such patients is a step toward both objectives. Some of the deterioration experienced in chronic disease patients occurs outside the view of their clinicians, and before the patient becomes overtly symptomatic. Home monitoring has been used for more than 20 years to detect deterioration ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
(22 reference statements)
1
2
0
Order By: Relevance
“…However, as indicated in one of the quotes included in the paper, insufficient coaching and familiarity with the platform could be one reason why this subset of patients did not engage with the platform. This was also supported in a recent study on extra device monitoring in patients with HF [ 28 ].…”
Section: Discussionsupporting
confidence: 76%
“…However, as indicated in one of the quotes included in the paper, insufficient coaching and familiarity with the platform could be one reason why this subset of patients did not engage with the platform. This was also supported in a recent study on extra device monitoring in patients with HF [ 28 ].…”
Section: Discussionsupporting
confidence: 76%
“…A recent study of in-home monitoring of vital signs in the intended use population of the device indicated that 73% of participants felt better about their health and had a better picture of their health as a result of using the device. 145 In the area of athletics, several novel wearable devices have been developed to track athletic performance. The Aura Band (Aura Devices, Wilmington DE, USA) is sold as an advanced fitness tracker that integrates several sensors (optical IR, accelerometer, bioimpedance electrodes) to present a full body composition analysis (fat, muscle mass, minerals, and hydration).…”
Section: Wearable Biomedical Devicesmentioning
confidence: 99%
“…Two disposable electrodes on the back side of the necklace are attached to the patient’s upper chest, where ECG and impedance waves are measured to elicit information about the heart rate, respiration rate, skin temperature, stroke volume, posture, and cardiac output. A recent study of in-home monitoring of vital signs in the intended use population of the device indicated that 73% of participants felt better about their health and had a better picture of their health as a result of using the device …”
Section: Bis and Telehealthmentioning
confidence: 99%